Analisis Evaluasi Sistem Pengendalian Intern Pengeluaran Kas Pada PT. Puduarta Insani Medan - Yenni Samri Juliati Nst; Amani Raudathul Jannah (AGHNIYA : Jurnal Ekonomi Islam, 2020)
Internal Control is a policy and procedure that protects company assets from misuse, ensuring that business information presented is accurate and ensures that laws and regulations have been followed. The purpose of this study is to find out whether the internal control system for cash disbursement has gone well. This type of research is descriptive qualitative. Data collection methods carried out are documentation and interviews. The sample in this study is cash disbursement at PT. Puduarta Insani Medan in 2013, 2014, and 2015. The results showed that the cash internal control system at PT. Puduarta Insani Medan has been going well, this can be marked by the existence of an organizational structure that already has a clear separation of responsibilities in each of its duties and authorities, the company carries out healthy practices in carrying out its duties and functions in each organization by using numbered forms and performing rotation if needed, the company also recruits employees whose quality is in accordance with the responsibilities and applies a strict authorization and recording system as well as good internal control.